Child and adolescent chronic fatigue syndrome/myalgic encephalomyelitis: where are we now?. Issue 4 (August 2019) - Gregorowski, Anna; Simpson, Jane; Segal, Terry Y.
Abstract : Purpose of review: The current review aims to determine the recent evidence regarding cause, impact, effective treatment and prognosis of children and young people (CYP) affected by chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) at a time when the National Institute for Clinical Excellence guidelines in the United Kingdom are being reviewed and more research is called for worldwide. Recent findings: CFS/ME is a debilitating illness with no clear cause. This review describes the heterogeneous clinical picture and the effects on the young person and family. Comorbidities such as mood disorders and pain are discussed including evidence for treatment. The various aetiological hypotheses are discussed and the precipitating factors identified. The evidence base is limited regarding effective treatment for CYP with CFS/ME, particularly the severely affected group. A large trial of online cognitive behavioural therapy with teenagers is being explored in the United Kingdom. The Lightning Process has been shown to be effective when added to medical care. Summary: Current evidence is hampered by different diagnostic criteria, the heterogeneous nature of the condition, and limited number of small studies. There is a clear need for more research and larger studies exploring the cause of and most effective treatment for CYP with CFS/ME.